(untitled) (English Language and Literature (JELL), 2026)
This study aims the portrayal of women as subalterns and their forms of resistance in Chitra Banerjee Divakaruni’s The Last Queen (2021). Drawing on postcolonial feminist theory and Spivak’s concept of the subaltern, it investigates how women are marginalized within patriarchal and colonial structures of Hindustani society during the British colonial era. Using a descriptive qualitative approach, data were drawn from characters’ narratives and dialogues. The findings reveal two key points: first, women are represented as subalterns through voicelessness, devaluation, and limitation, reflecting overlapping oppressions of gender, class, religion, and colonial domination; second, subaltern women actively resist through political and intellectual means, though such resistance largely fails to dismantle the prevailing structures of domination